The Conceptual Access-NeTwORk (CANTOR) Thesis: Theorizing the Development or Success of New Internet-Based Products, Services, or Technologies - La Shun L. Carroll (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
For any new internet-based product, service, or technology to succeed, it must satisfy the criterion of providing access to or creating a network of possible users, products, and services. This is the Conceptual Access-Network (CANTOR) Thesis proposed. In addition to the main issues of success and how and why internet technology evolves, the principle can also meet the objective of explaining what underlies a range of traditional and nontraditional technologies beyond the internet. Through qualitative exploration, the tenets of the access-network thesis are applied to natural and synthetic forms of endocrine substances including insulin and highways. A discussion of technologically generated knowledge is included, as well as how phenomenotechnique can be used to establish a communication path between technology and what it produces. Dr. Stanley Milgram's intimate stranger phenomenon which was first explored in 1967, before the internet existed, will ultimately be distorted by the future of internet-based technologies.  As previously discovered or established concepts are combined or permuted, the future will display numerous manifestations, combinations, and permutations. We conclude that successful internet-based products, services, or technologies simply would not work without an access network. From this article, we have gained a better understanding of the current development stage of internet-based products and technology, thereby enabling society to better anticipate the future of internet-based products and technology, highlight significant ethical considerations, and avoid unwanted outcomes.